Analisis Biaya Produksi dan Harga Pokok Penjualan pada Pabrik Sari Gurih Baru 568 - Rafika Chairani; Indy Ramadhani Putri Pountung; Susan Leoni; Yuni Astuti Tri Tartiani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to analyze the cost structure of production and the cost of goods sold (COGS) at Sari Gurih Baru 568 Tofu Factory. The research employs a qualitative descriptive method, gathering data through in-depth interviews and non-participant observation. Using this approach, the study explores cost components that influence production efficiency and COGS determination. Through this analysis, the research provides in-depth insights into cost allocation, resource management, and opportunities to enhance cost-efficiency in production. The findings are expected to support improved decision-making in cost management and pricing strategies within the Small and Medium Enterprises (SME) sector.